Nurses’ Perceptions and Expectations on The Implementation of Career Ladder in Public Hospitals in Makassar - Meyke Tiku Pasang; Kusrini Kadar; Rosdiana Natzir (Faculty of Nursing, Universitas Hasanuddin, 2017)
Introduction: Nurses as professionals must provide services in accordance with the competence and authority possessed either individually or as part of a hospital team. Thus, there is a need to manage the resources of nursing such as the professional career development system for nurses. The study aimed to identify the perception and expetation of the nurses on the implementation of career ladder in two hospitals in Makassar city. Method: This research used quantitative method with the cross sectional design. There were 105 nurses from Hasanuddin University Hospital and 212 nurses from Dr. Wahidin Sudirohusodo Hospital involved as samples in this study. The samples were chosen using the disproportionate stratified random sampling technique. The data were collected through questionnaires to find out the nurse perception including some open ended question to explore the nurses expectation from this career ladder program. The data were analyzed using descriptive statistic and mann-whitney to seee the differences perception between the groups. Result: The result revealed although that mean of perception about the implementation of career ladder in two hospitals are considered good (m=3.70 dan m=3.94), there was differences of nurses perception in both hospitals (p=0.00). Conclusions: Meanwhile, the result of open-ended questions about nurses' expectation about the implementation of the career ladder emphasized that there should be a schedule for training for their professional improvement. Evaluation for further assessment for higher levels of career ladder also considered important for the nurses in both hospitals. Furthermore, the rewards or incentives for the nurses received shold be appropriate according to the career levels. In conclusion, the implementation of career ladder program in both hospitals have been considered good, however, the hospitals need to support the nurses and pay attention to factors that could influence the nurses satisfaction of the program.